Pengembangan Materi Ajar Berbasis Ekowisata Mangrove dalam Pembelajaran IPA: Review - Hariani, Riri (Lembaga Pendidikan, Penelitian, dan Pengabdian Kamandanu, 2024)
Science learning in schools often emphasizes rote memorization of content, rather than applying knowledge in real-life contexts. The objective of this research is to explore the development of teaching materials based on mangrove ecotourism and their effectiveness in science education. The method employed in this study is literature review. Articles were reviewed through a national-level literature search using selected sources (databases), namely Google Scholar. The search terms included